Direct Tax and Income Redistribution: Array - Akogo, Obehioye; Akadakpo, Bukola Adefunke (The Journal of Accounting and Management, 2022)
The aim of this paper is to examine the effect of direct tax as a tool for income redistribution in Nigeria. The research design employed in the study is the longitudinal design. The population and sample of this study focused mainly on direct taxes which include; petroleum profit tax (PPT), personal income tax (PIT), company’s income tax (CIT) and education tax (ED), that are domicile in Nigeria. The timeframe spanned 1990-2020. Data was sourced from world statistics, federal inland revenue service and central bank statistical bulletin. The data for the study was analysed using the error correction model. The Result from the inferential statistic employed revealed that company income tax and education tax had no significant effect on income redistribution; while personal income tax and petroleum profit tax had significant effect on income redistribution. Furthermore, personal income tax had positive effect on income redistribution while petroleum profit tax had negative effect on income redistribution. The study recommended that there should be introduction and proper implementation of a luxury tax system where the rich will be made to pay tax consuming more luxury goods than the poor. The revenue generated from luxury tax should be used to implement free education and medical services for low-income earners. Education taxes should be used to fund scientific projects and used to sponsor low-income earners abroad.